Pemberdayaan Masyarakat Lokal Melalui Edukasi Budaya Jepang Sebagai Daya Tarik Wisata di Kampung Sakura Kota Batu Jawa Timur - Nugroho, Rahadiyan Duwi; Suryawati, Cicilia Tantri; Andarwati, Titien Wahyu; Pujimahanani, Cahyaningsih; Putri, Sitty Najwa Amalia; Fayadh, Satria Ammar; Putri, Alvina Salshabilla Linjani (Jurnal Pengabdian UNDIKMA, 2025)
This community service program aims to enhance the understanding and skills of tourism managers about Japanese culture as a tourist attraction in Kampung Sakura Batu, East Java. The service method employs Participatory Action Research (PAR) oriented towards community empowerment. The evaluation instruments utilize questionnaires and interviews, with qualitative descriptive data analysis techniques to assess the outcomes. The results of this service activity show an increase in knowledge among Kampung Sakura managers about several Japanese cultures, including how to wear a Yukata correctly, perform a tea ceremony, make sushi, arrange Japanese flowers (Ikebana), and understand simple Japanese conversations that can be used to welcome tourists visiting Kampung Sakura.